SATISFACTION LEVEL OF PALM OIL FARMERS TOWARDS PALM OIL RAM SERVICES IN PERLABIAN VILLAGE, KAMPUNG RAKYAT DISTRICT, LABUHAN BATU SELATAN REGENCY - Gustina Siregar; Muhammad Ikhsan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to identify RAM service attributes based on the level of importance and performance according to oil palm farmers and to determine the level of farmer satisfaction with the services provided by RAM oil palm in Perlabian Village, Kampung Rakyat District. This study was conducted in March 2025 on 105 respondents. The research location was determined purposively. The data analysis methods used were Descriptive Analysis, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The results are that the service attributes that need to be improved by marketing institutions are the ability of RAM in delivering information, the ability of RAM in providing solutions, the honesty of RAM in the services provided, RAM prioritizing farmers and the availability of RAM in receiving suggestions. The CSI value of farmer respondents for marketing institutions was 72.86%. Overall, the level of satisfaction of oil palm farmers with RAM marketing services is in the Satisfied category.